Active sites in modified copper catalysts for selective liquid phase dehydration of aqueous glycerol to acetol - Mane, Rasika B.; Yamaguchi, Aritomo; Malawadkar, Atul V.; Shirai, Masayuki; Rode, Chandrashekhar V. (RSC Advances, 2013)
We report here the influence of oxides of various metals viz. Ba, Mg, Zr, Zn, Al, and Cr in modified copper catalysts, on the formation of different copper species and acid sites responsible for dehydration of aqueous glycerol to acetol. These catalysts were prepared by a co-precipitation method, among which the catalysts having higher acid strength and predominant Bronsted acidity (Cu-Mg, Cu-Zr and Cu-Al) gave the highest acetol selectivity (76-92%), while the catalysts with lower acidity such as Cu-Zn showed very poor (25%) selectivity to acetol in spite of the highest conversion of 68%. Nevertheless, catalysts exhibiting higher activity and acetol selectivity also showed the presence of metallic Cu confirmed by XRD and XANES-EXAFS characterization. Based on these results, two different catalytic pathways have been proposed highlighting the role of Lewis and Bronsted acidity along with the metal sites in individual steps of glycerol dehydration reaction.